Thrips (Thysanoptera) of avocado (Persea americana) in Nayarit, Mexico - CAMBERO-C., OCTAVIO J.; JOHANSEN-N., ROBERTO; RETANA-S., AXEL; GARCÍA-M., OSWALDO; CANTÚ-S., MARIO; CARVAJAL-C., CARLOS (Revista Colombiana de Entomología, 2010)
The species of thrips associated with Hass avocado orchards was determined, and their importance as pests or predators was established. Research was carried out in the municipality of Xalisco, Nayarit, Mexico, in three commercial orchards located at different altitudes: “La Carbonera”, “El Carrizal” and “Oreja de Raton.” Weekly collections were carried out over a period of 24 months, using three sampling techniques: blanketing, netting and knockdown. A total of 3,698 adult thrips were captured. The greatest capture was at “La Carbonera” (40.50%), the intermediate at “Oreja de Raton” and the lowest at “El Carrizal” (20.76%). The knockdown technique obtained the highest number of thrips, followed by netting and blanketing, respectively. A total of 725 thrips were identified, resulting in 40 species. Franklinothrips orizabensis was the most represented species (21.7%), followed by Pseudophilothrips perseae (15.2%) and Franklinothrips lineatus (14.3%). The other 37 species had percentages ranging from 0.13 to 8.65. In this diversity, 11 species are phytophagous, seven predaceous and 22 visitors.